The Effect of Cash Management and Operational Cost Control on Business Profit: Evidence from Agung Trading Business in Tanjung Menang Jarai Village - Sholikhatamara Sholikhatamara; Elvera Elvera; Ruaman Yudianto (The Future of Education Journal, 2026)
The purpose of this study is to determine and describe the Effect of Cash Management and Operational Cost Control on Business Profit at "Usaha Dagang Agung" in Tanjung Menang Jarai Village. This type of research is Quantitative. The method used is saturated sampling. Primary data was obtained from Cash Management, Operational Cost Control, and Business Profit at "Usaha Dagang Agung" in Tanjung Menang Jarai Village. Secondary data was obtained through the Unrem Description of "Usaha Dagang Agung", Cash Management List, Operational Cost Control List. Business Profit List. The result is a multiple linear regression constant: -51.060 regression coefficient of Cash Management variable of 0.695. Based on the results of the regression coefficient analysis of the influence of Cash Management and Operational Braya Control on Business Profit, the multiple linear regression value is: Y = -51.060 -0.695 X1 -0.943 X2, constant value of -51.060. The regression coefficient value of Cash Management is positive at 0.695. This shows that each Cash Management unit will increase Operating Profit by 0.695 (positive effect). Based on the t-test results on the variables, the calculated t-value is 3.814 with a significance level of 0.1001. Meanwhile, the Operational Cost Control variable (X2) produces a calculated t-value of 3.666 with a significance value of 0.001. Because the significance values ​​of the two variables are smaller (0.001 <0.05 and 0.001 <0.05), it can be concluded that both variables X1 and X2 have a partial significant effect on Operating Profit (Y).